CARBON PASTE ELECTRODE MODIFIED WITH CAFFEINE MOLECULARLY IMPRINTED POLY(GLUTAMIC ACID) FOR SIMULTANEOUS DETERMINATION OF CAFFEINE AND PARACETAMOL BY VOLTAMMETRY - AYU FITRIANI - NIM: 20516011 , NUR
The combination of caffeine and paracetamol is effective and safe to use as an analgesic drug for the relief pain. However, overdosed of caffeine and paracetamol can cause harmful side effects in body. Determination of caffeine and paracetamol for quality control in drugs is important. The method that can be used for simultaneous determination of caffeine and paracetamol is voltammetry. Oxidation of caffeine using conventional bare electrodes gives relatively low current response. In this research, carbon paste electrode (CPE) was modified with molecularly imprinted polymers (MIP) for voltammetric determination of caffeine and paracetamol had been developed. The modification of MIP on the surface of CPE was assembled by electropolymerization process using cyclic voltammetry (CV) technique in glutamic acid solution as functional monomer and caffeine as template in phosphate buffer solution of pH 7. The measurements of caffeine and paracetamol were performed using differential pulse voltammetry (DPV) in perchloric acid solution as supporting electrolyte. Measurement of caffeine using MIP-CPE show that modification can improve the current response. The effect of monomer and template concentrations, number of electropolymerization cycles, removing of template cycles and scan rate was optimized. MIP-CPE shows good repeatability with %RSD of 5,32% for caffeine and 3,43% for paracetamol (n=40). EPK-MIP calibration curve provides a linear response in the concentration range of 10 - 600 μM with the detection limit of 3,43 μM for caffeine and the concentration range of 1 - 900 μM with the detection limited of 0,43 μM for paracetamol. The results of determination in pharmaceutical formulation samples with MIP-CPE were in good agreement with those HPLC and spectrophotometry method with agreement at 95 % confidence level.